«Doing the robberies and evil that they can like corsairs jumping ashore». Privateer Raids in the Caribbean. The Case of William Parker on Campeche, 1597 - De la O Torres, Rodrigo Alejandro (Revista de historia., 2023)
In May 1597, Captain William Parker, along with half a hundred men, raided the town and port of San Francisco de Campeche in order to obtain some kind of booty. The purpose of this essay is to analyze this case in order to approach the configuration and characteristics of this raid based on the violence that occurred in it. To account for this process implies addressing the contexts that gave rise to the violence, as well as unveiling the subjects involved and their actions within the framework of this attack. Therefore, this case study is also a micro analysis proposal. Our presentation includes the following sections: a) frameworks of rationality, b) intentionalities, c) deployment of violence and d) conclusions. We assert that the raids were multidimensional, multifaceted and historically situated violent social events.